Congenital bile duct cystic dilatation (part 1). Intrahepatic bile ducts (Revista Argentina de Cirugía, 2021)
Caroli’s disease is a rare condition, and its diagnosis requires high level of suspicion. The disease may affect one segment, one lobe or the entire liver, and may result in repeated episodes of cholangitis. The disease can be managed using different therapeutic approaches ranging from medical treatment to liver transplantation. In this paper we report 3 cases with review of the literature and propose a modification of the classification by Alonso-Lej modified by Todani which we believe may be useful to guide treatment.
Keywords: Caroli disease; classification; treatment